2017
DOI: 10.1002/berj.3274
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent moral judgement: A study of UK secondary school pupils

Abstract: Despite a recent world-wide upsurge of academic interest in moral and character education, little is known about pupils' character development in schools, especially in the UK context. The authors used a version of the Intermediate Concept Measure for Adolescents, involving dilemmas, to assess an important component of character-moral judgement-among 4053 pupils aged 14-15. Data were generated in 33 UK schools of varying types between February 2013 and June 2014. Results showed that compared with US samples, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 33 publications
(61 reference statements)
1
21
0
2
Order By: Relevance
“…These findings suggest that a naïve functionalist view of religion as social control (or even educational indoctrination), may not account for the importance of the individual salience of religion as a principal factor in the relationship between religion and moral choice. This is perhaps reflected in findings of recent research that suggests religious practice and identification are predictors of higher scores in tests of moral reasoning (Walker, Thoma, Jones, & Kristjánsson, 2017). Our conclusion is strengthened by the range of adjusted variables included in the analyses that could have otherwise confounded this relationship, such as socio-economic status, age, sex and school-type.…”
Section: Discussionsupporting
confidence: 56%
“…These findings suggest that a naïve functionalist view of religion as social control (or even educational indoctrination), may not account for the importance of the individual salience of religion as a principal factor in the relationship between religion and moral choice. This is perhaps reflected in findings of recent research that suggests religious practice and identification are predictors of higher scores in tests of moral reasoning (Walker, Thoma, Jones, & Kristjánsson, 2017). Our conclusion is strengthened by the range of adjusted variables included in the analyses that could have otherwise confounded this relationship, such as socio-economic status, age, sex and school-type.…”
Section: Discussionsupporting
confidence: 56%
“…Among Spanish youth ages 6 to 11, participation in chess clubs was related to significant gains in individuals' understanding of others (i.e., moral cognition) over the course of a year whereas no gains were observed with peers participating in soccer or basketball (Aciego et al 2012). Researchers in the United Kingdom found that compared with nonparticipants, middle school adolescents (ages 14-15) who participated in charity, music/choir, and drama activities reported better moral judgment though there were no differences between nonparticipants and participants in art, debating, or sports (Walker et al 2017). While studies examining specific type/profile of activities found differences in youth's behaviors, studies that used too broad of a categorization of activity type (e.g., all sport activities compared to all nonsport activities) failed to detect such differences during the childhood years (Molinuevo et al 2010) or early adolescence (7th grade; Villarreal and Gonzalez 2016).…”
Section: Moral Behaviors and Cognitionsmentioning
confidence: 99%
“…Some authors report significant relationships between religiosity (as measured by religious belief/commitment) and MR (Wimalasiri, 2001(Wimalasiri, , 2004Coleman & Wilkins 2002;Drake, Griffin, Kirkman & Swann, 2005). Walker, Thoma, Jones, and Kristjánsson (2017) report that religious practice and religious identification predict higher scores of MR. While others point to non-significant relationships between MR and religious affiliation (Maeda, Thoma, & Bebeau, 2009) and religious participation (Wilhelm, 2004).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%